Self‐Assembly of Decoupled Borazines on Metal Surfaces: The Role of the Peripheral Groups. Issue 37 (30th July 2014) - Kalashnyk, Nataliya; Ganesh Nagaswaran, Praveen; Kervyn, Simon; Riello, Massimo; Moreton, Ben; Jones, Tim S.; De Vita, Alessandro; Bonifazi, Davide; Costantini, Giovanni
Abstract Two borazine derivatives have been synthesised to investigate their self‐assembly behaviour on Au(111) and Cu(111) surfaces by scanning tunnelling microscopy (STM) and theoretical simulations. Both borazines form extended 2D networks upon adsorption on both substrates at room temperature. Whereas the more compact triphenyl borazine 1 arranges into close‐packed ordered molecular islands with an extremely low density of defects on both substrates, the tris(phenyl‐4‐phenylethynyl) derivative 2 assembles into porous molecular networks due to its longer lateral substituents. For both species, the steric hindrance between the phenyl and mesityl substituents results in an effective decoupling of the central borazine core from the surface. For borazine 1, this is enough to weaken the molecule–substrate interaction, so that the assemblies are only driven by attractive van der Waals intermolecular forces. For the longer and more flexible borazine 2, a stronger molecule–substrate interaction becomes possible through its peripheral substituents on the more reactive copper surface.